Study guides

☆☆☆☆☆

Q: What is 4x minus 2x?

Write your answer...

Submit

Related questions

4x - 2x = 2x

7x2 -4x -5x2 +2x = 2x2 -2x

2x(2x - 1)

(2x-1)(2x-1) = 4x^2 -4x + 1

(2x - 1)(4x + 1)

(2x - 1)(2x + 1)

-x2+2x

3x - 5x + 4x = -2x +4x = 2x

Let 6x - 2x - 9 = a, where a is an arbitrary constant. Then 4x - 9 = a 4x = a+9 x = (a+9)/4

2x+7x-10=4x+3-2x 9x-10=2x+3 7x=13 x=13/7ans

4x - 7 = 2x + 5 2x - 7 = 5 2x = 12 x = 6.

4x2 - 9 = (2x + 3)(2x - 3)

(2x - 1)(2x + 5)

(2x - 9)(2x +9)

(2x - 9)(2x - 9) or (2x - 9)2

(2x - 9)(2x - 9) or (2x - 9)2

(2x - 4)(2x + 3) The key is to look for all the factor pairs of 12.

8x^2 + 6x - 5 = 8x^2 + 10x - 4x - 5 = 2x * (4x + 5) - (4x + 5) = (2x -1) * (4x + 5)

(4x-8)(2x+2)

There is no rational factorisation.

Assuming there are no parentheses:2 times X - 1 + 4X - 6 + 2X =2X - 1 + 4X - 6 + 2X =2X + 4X + 2X - 1 - 6 =8X - 1 - 6 =8X - 7

if you mean (3/(2x-5))(21/(8x2-14x-15)) you would get (63/( (2x-5)(4x+3)(2x-5) ) simplified more would be 63/ ( (2x-5)2(4x+3) )

(2x+5)(4x-7)

x= Negative 4

8x2 + 6x - 9 = 8x2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)